Implementasi Kebijakan Penanggulangan Banjir di Kota Tangerang Selatan - Nadia Wulandari; Abdullah Qiqi Asmara (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This research focuses on the implementation of flood management policies in South Tangerang City with suboptimal flood management problems. The problems that were found were that the coordination carried out by stakeholders was tentative, there were obstacles in communication on the condition of the social environment, expecially in terms of public awareness of protecting the environment, was still lacking because rubbish was still found in rivers and canals. The aim of this research is to determine the extent of implementation of flood management policies in South Tangerang City. This research uses a qualitative approach with descriptive methods, and data is obtained trought observation, interviews and documentation. This research uses the Van Meter and Van Horn theory with 6 (six) indicator, namely: a) Policy Size and Objectives; b) Resources; c) Characteristics of The Implementing Agent; d) Attitude and Tendencies; e) Inter-Organizational Communication and Implementation Activies; f) Economic, Social and Political Environment. The result of the study show that policy measures and standards are appropriate but there needs to be an increase in disaster outreach and training. Then the quantitiy or number of Task Forces to go into the field is still insufficient. The availability of an organizational structure and regulations responsible for implementing flood management is quite good. Policy implementers understanding of flood management policies in quite good and has received a positive response from policy implementers. Apart from that, the communication that exists between OPDs and village officials is quite good, characterized by delibration. The economic, social and political environmental conditions are quite good, but there needs to be an increase in public awareness of protecting the environment by not throwing rubbish into rivers or waterways.